SENI LARASMADYA DESA WONOREJO KABUPATEN SUKOHARJO - Panggiyo Panggiyo (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2004)
Larasmadya contains religious values and promotes moral behavior according to the Islamic religion, while at the same time presenting an expression of art. For this reason, although there is a dichotomy between the older and younger generations, the art of larasmadya in Wonorejo continues to exist.This art form originated from a Kiyai, or religious leader, by the name of Imam Suhada, who was an expert in Islam and supernatural powers from the village of Wonorejo. The existence of larasmadya in the village of Wonroejo is quite unique in that it has been passed down from generation to generation within one family of descendants.Keywords: Larasmadya, eksistensi.